Imaging Findings in Agenesis of the Dorsal Pancreas. Report of Three Cases - Mohapatra, Manoranjan; Mishra, Sanjeet; Dalai, Prakash Chandra; Acharya, Sachin Dev; Nahak, Brundaban; Ibrarullah, Md; Panda, Kedarnath; Mishra, Sasanka Sekhar (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; line-height: 115%; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; line-height: 115%; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Agenesis of the dorsal pancreas is rare. The dorsal pancreatic agenesis is described in two forms, the partial and the complete form. Patients with this anomaly may be asymptomatic or may present with diabetes mellitus, epigastric pain, acute or chronic pancreatitis. Case report We report the computed tomography (CT), magnetic resonance imaging (MRI) and magnetic resonance cholangiopancreatography (MRCP) findings in three cases with dorsal pancreatic agenesis, one with partial and the other two with complete form. Speckled calcification at pancreatic head was observed in one patient. Lateral contour lobulation of pancreatic head which is seen in one third of normal population is believed to be due to variation in fusion between ventral and dorsal pancreas. In contrast, we observed lateral contour lobulation of pancreatic head in a case of complete agenesis of the dorsal pancreas where structures derived from dorsal pancreas are undeveloped. The ventral and dorsal pancreatic duct lengths were measured on MRCP images and we observed that in partial agenesis, the duct of Wirsung was shorter in length, compared to the duct of Santorini. The duct of Wirsung was relatively longer in cases of complete agenesis of the dorsal pancreas. Conclusion The CT, MRI and MRCP findings in dorsal pancreatic agenesis and the relationship between the length of ventral duct with the type of dorsal pancreatic agenesis will provide a new insight into this particular anomaly.